A Cell-Centered ALE Method with HLLC-2D Riemann Solver in 2D Cylindrical Geometry (Journal of Computational Mathematics, 2021)
This paper presents a second-order direct arbitrary Lagrangian Eulerian (ALE) methodfor compressible flow in two-dimensional cylindrical geometry. This algorithm has half-facefluxes and a nodal velocity solver, which can ensure the compatibility between edge fluxesand the nodal flow intrinsically. In two-dimensional cylindrical geometry, the control volume scheme and the area-weighted scheme are used respectively, which are distinguishedby the discretizations for the source term in the momentum equation. The two-dimensionalsecond-order extensions of these schemes are constructed by employing the monotone upwind scheme of conservation law (MUSCL) on unstructured meshes. Numerical results areprovided to assess the robustness and accuracy of these new schemes.